Academic Procrastination: The Case of Mexican Researchers in Psychology - Vargas, María Antonia Padilla (American Journal of Education and Learning, 2017)
Procrastination is defined as the tendency to delay the performance of tasks that have a deadline date. Between 70 and 95% of university students procrastinate occasionally, and 20-40% do so chronically. Procrastination affects both people’s health and the quality of their work. The objective of the present study was to identify whether Mexican researchers in psychology procrastinate (no similar studies were found during a literature review), and determine the academic, work-related and health effects of this behavior. A total of 221 Mexican psychology researchers participated, 91 men and 131 women, aged 20-65 years (by answering an on-line questionnaire designed ex profeso). Results showed the following: 91% of respondents reported procrastinating; the activity with the highest levels of procrastination was writing reports and/or academic articles (63%); 29% reported that procrastination generated anxiety; 42% observed that it damages their health; 18% mentioned that procrastinating reduced the quality of their work; and 17% reported that it had had many negative effects on their lives. This article discusses the importance of identifying the factors that propitiate academic procrastination given the negative effects of this behavior on researchers’ health and work quality.